Reasons for the overly optimistic beliefs of parents of children with diabetes - Freckleton, E.; Sharpe, L.; Mullan, Barbara (Blackwell Scientific Publications, 2014)
Aims: The purposes of this study are to investigate parents' beliefs about the likelihood of diabetes outcomes for their child, the reasons that they give for these beliefs and the relationship between the beliefs and parental psychopathology. Methods: Seventy-one mothers of children with diabetes completed a questionnaire about the likelihood of certain diabetes outcomes and measures of psychopathology. Both qualitative and quantitative data were collected at a single time point. Results: Mothers generally held very optimistic views about their children's future, and this was associated with less maternal depressive symptoms. Mothers typically used their previous experiences and belief that diabetes is controllable to justify optimistic beliefs about short-term consequences. In contrast, formation of mothers' views on long-term consequences generally relied on information from a variety of sources. Conclusion: The results suggest that it is usual and helpful for mothers of children with diabetes to hold overly optimistic views about their children's futures. Medical evidence appears to have little influence on mothers' beliefs about likely outcomes for their children.